(untitled) (Bangladesh Journal of Medical Physics, 2013)
Focused Impedance Method (FIM) based on 8, 6 and 4 electrode configurations have been innovated and developed for measuring the electrical impedance of a localised zone in a volume conductor, all based on tetrapolar impedance technique. The zone localization in FIM has been visualized through equipotential distributions, current density at the target point and perturbation produced at the potential measuring electrodes. The predicted behaviour has been verified though phantom measurements and analytical techniques by different groups. FIM is particularly sensitive and useful if the electrical impedance of a target object in the sensitive zone changes between two sets of measurements. This can be either due to a physical change in the target object, or, if its impedance has frequency dependence, through a change in the measurement frequency. In medical applications FIM is being developed for studying stomach and bladder emptying, localized lung function, detection of cervical and oral cancer, etc. FIM may have applications in industry to study physical mixtures of liquids and gases in pipelines and tanks, in geology to detect groundwater and other minerals, in oceanography, and in many other applications. Thus FIM appears to have a huge potential for application in different areas. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14689 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 67-74